Evolutionary ecology of microbial populations inhabiting deep sea sediments associated with cold seeps - Xiyang Dong; Yongyi Peng; Muhua Wang; Laura Woods; Wenxue Wu; Yong Wang; Xi Xiao; Jiwei Li; Kuntong Jia; Chris Greening; Zongze Shao; Casey R. J. Hubert (Nature Communications, 2023)
Little is known about genetic heterogeneity within deep sea cold seep microbial populations. From examining 39 abundant microbial species identified in sediment layers below the sea floor and across six cold seep sites, this study reports that their evolutionary trajectories are depth-dependent and differ across phylogenetic clades.